Recalibrating Librarians’ Service Ethic in the COVID-19 Pandemic - Brown, Laila (Qualitative and Quantitative Methods in Libraries, 2020)
Though the service ethic resonates deeply with many in librarianship, the COVID-19 pandemic—and accompanying mandate of some library governing bodies that library buildings stay open and staff report to work on site—has underlined a need to critically reassess it. In interrogating conceptualizations of librarianships’ service ethic, I aim to problematize the association of service with subservience, challenge assumptions about women’s outsized role in the domain of caring, and reaffirm a feminist approach to service work as central to librarianship. I employ a feminist framework to shift the focus of service from hierarchical to mutually empowering relationships. This reframing may make progress towards enhanced appreciation of libraries’ and librarians’ worth to society, and by extension, that of all service oriented, women-intensive professions.